Integrated nutrient management studies in mustard (Brassica juncea L.) in Southern Haryana: INTEGRATED NUTRIENT MANAGEMENT STUDIES IN MUSTARD IN SOUTHERN HARYANA - ROHIT; HANSRAJ SHIVAN; R S YADAV; RAJKUMAR SHARMA; AMIT KUMAR; MANJEET; ASHISH KUMAR YADAV (Journal of Oilseeds Research, 2024)
A field experiment was conducted to study the influence of integrated nutrient management on mustard (Brassica juncea). The experiment was conducted in randomised block design with thirteen treatments. Highest plant height, branches/plant and higher dry matter accumulation were recorded with application of 100% NPK + 5 t Vermicompost + 40 kg S + Azotobacter followed by 75 % NPK + 5 t Vermicompost + 40 kg S + Azotobacter. Significantly higher yield and yield attribute traits like seed/siliqua, siliqua length and number of siliqua/plant/ were recorded with 100 % NPK + 5 t Vermicompost + 40 kg S + Azotobacter which was statistically at par with 75 % NPK + 5 t Vermicompost + 40 kg S + Azotobacter, 100 % NPK + 5 t Vermicompost + 40 kg S and 100 % NPK + 5 t Vermicompost. All integrated nutrient management treatments significantly increased the net returns in mustard. the highest net returns of ` 50,379 was recorded in the treatment with application of 100 % NPK + 5 t Vermicompost + 40 kg S + Azotobacter over others.